Instrument evaluation of conspiracy theory about COVID-19: Exploratory factor analysis and confirmatory factor analysis - Ahmad Fauzi; Muhammad Saefi; Widi Cahya Adi; Evi Kristiana; Nurlita Lestariani (Institute of Advanced Engineering and Science, 2022)
Students’ beliefs toward conspiracy theory (CT) of COVID-19 can be the indication of science education quality. However, a validated instrument to measure the level of students’ acceptance on the CT about COVID-19 still remains unexplored. This study aimed to evaluate the questionnaire of CT about COVID-19. The questionnaire consisted of 14 items and delivered online to the 400 students of Biology education in Indonesia. The data was analyzed using exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). All items have standard deviation between 1.60 and 2.63, but one item was revealed to have insignificant correlation. The EFA result indicated that the other 13 items had loading factor 0.5 and were categorized into three dimensions. The third dimension was eliminated after the administration of CFA due to only one item in the dimension (λ>0.5). There were three items in the first dimension and two items in the second dimension resulted in λ<0.5. The correlated model from CFA disclosed good values of goodness of fit (GOF), χ2/df=2.527, root mean square error of approximation (RMSEA) standardized root mean square residual (SRMR)=0.014, comparative fit index (CFI)=0.964, goodness-of-fit index (GFI)=0.969, adjusted goodness of fit (AGFI)=0.940, Tucker-Lewis index (TLI)=0.947, and normed fit index (NFI)=0.943. Therefore, the questionnaire is strongly recommended to measure the level of students’ beliefs toward the CT of COVID-19.